Preparation method and application of perovskite thin film with high humidity stability
By modifying the MAPbI3 perovskite layer by using perfluoro (4-methyl-2-pentene) as an additive in the preparation of perovskite films, the perovskite films are solved due to the high humidity and the presence of oxygen in the air environment. The defect problem significantly improves the stability of the film and the photoelectric conversion efficiency of solar cells.
Patent Information
- Application Number
- CN202411417114.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-11
- Publication Date
- 2025-02-07
AI Technical Summary
During the preparation of perovskite films in an air environment, surface/body defects are easily caused by high humidity and the presence of oxygen, which damages its power conversion efficiency and stability.
Perfluoro(4-methyl-2-pentene) (C6F12) is used as an additive and is introduced into the green antisolvent. The MAPbI3 perovskite layer is modified by the mutually soluble passivation method of small liquid molecules to form a modified antisolvent to improve the Stability of the film.
It significantly improves the crystallinity, grain size and moisture resistance of perovskite films, enhances the stability and photoelectric conversion efficiency of solar cells, and can maintain 80% of device performance in a high humidity environment.
Smart Images

Figure CN119403416A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of new energy materials, and in particular relates to a preparation method of a perovskite film with high humidity stability and application thereof. Background Art
[0002] Perovskite solar cells (PSCs) processed in air environments have attracted the interest of researchers around the world due to their simple and economically feasible production methods. As early as 2009, researchers began to study PSCs. After more than ten years of development, its highest world certified record of power conversion efficiency (PCE) has been rapidly improved from the initial 3.8% to 26.7%. Despite this, there are often many unfavorable factors in the preparation process of perovskite films in air environments, resulting in an increase in film defects. For example, high humidity levels and the presence of oxygen may cause many surface / bulk defects in perovskite crystals during nucleation and growth, seriously damaging their power conversion efficiency (PCE) and the overall stability of the device.
[0003] Antisolvent engineering is one of the many ways to introduce additives into the perovskite light absorption layer. Because the preparation process of perovskite films often uses antisolvents such as ethyl acetate (EA) and diethyl ether (DE) that are miscible with the deposition solvent in the precursor solution but insoluble in the perovskite salt to adjust its surface morphology and crystallization process. However, some commonly used antisolvent additives have many disadvantages, such as being difficult to dissolve in organic solvents resulting in low concentrations, a small number of functional groups inside the molecule making it difficult to form effective bonds with the perovskite, and their own performance is not outstanding and excellent enough. Therefore, in order to finely modify MAPbI 3 For the perovskite layer, we used a liquid phase small molecule mutual dissolution passivation method, that is, the additive perfluoro(4-methylpent-2-ene)(C 6 F 12 ) is incorporated into a green and environmentally friendly anti-solvent. Summary of the invention
[0004] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.
[0005] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.
[0006] Therefore, the purpose of the present invention is to overcome the deficiencies in the prior art and provide a method for preparing a perovskite film with high humidity stability.
[0007] In order to solve the above technical problems, the present invention provides the following technical solution: a method for preparing a perovskite film with high humidity stability, characterized in that: comprising:
[0008] MAPbI 3 The perovskite precursor solution was once spin-coated on the electron transport layer and a modified anti-solvent was added 10 s before the end of the spin-coating process, and then subjected to thermal annealing treatment;
[0009] Wherein, the MAPbI 3 The perovskite precursor solution includes a solute and a solvent, wherein the solvent is a mixed solvent of N,N-dimethylformamide and dimethyl sulfoxide, and the solute is lead iodide and methylamino iodide; the modified anti-solvent is a solvent containing C 6 F 12 of ethyl acetate.
[0010] As a preferred embodiment of the preparation method of the present invention, wherein: 6 F 12 The concentration is 0.1~6vol%.
[0011] As a preferred embodiment of the preparation method of the present invention, the volume ratio of N,N-dimethylformamide to dimethyl sulfoxide in the solvent is 6:1 to 9:1, and the molar ratio of lead iodide to methylamino iodide in the solute is 1:1.
[0012] As a preferred embodiment of the preparation method of the present invention, wherein: the MAPbI 3 The preparation method of the perovskite precursor solution comprises: mixing a solute with a solvent, heating the mixture at 55° C. to 65° C., and stirring the mixture at a rotation speed of 200 to 500 rpm for 0.5 to 2 hours.
[0013] As a preferred embodiment of the preparation method of the present invention, the spin coating conditions are as follows: a rotation speed of 2000 rpm, a time of 10 s, a rotation speed of 3000 rpm, and a time of 25 s.
[0014] As a preferred embodiment of the preparation method of the present invention, the annealing temperature is 90° C. to 110° C., and the annealing time is 10 to 40 minutes.
[0015] As a preferred embodiment of the preparation method of the present invention, wherein: the modified anti-solvent and MAPbI 3 The volume ratio of the perovskite precursor solution is 10:7 to 50:7.
[0016] Another object of the present invention is to overcome the deficiencies in the prior art and provide a perovskite film with high humidity stability, characterized in that the thickness of the perovskite film is 200 to 600 nm.
[0017] Another object of the present invention is to overcome the deficiencies in the prior art and provide a perovskite film with high humidity stability for use in perovskite solar cells.
[0018] As a preferred embodiment of the application of the present invention, the perovskite solar cell comprises an anode, an electron transport layer, a photoactive layer, a hole transport layer and a cathode; wherein the photoactive layer is between the anode and the cathode, the electron transport layer is between the anode and the photoactive layer; the hole transport layer is between the cathode and the photoactive layer; the anode is ITO, the electron transport layer is SnO 2 , the photoactive layer is MAPbI 3 The hole transport layer is Spiro-OMeTAD, the cathode is Ag, and the complete device structure of the perovskite solar cell is Glass / ITO / SnO 2 / MAPbI 3 / Spiro-OMeTAD / Ag.
[0019] Beneficial effects of the present invention:
[0020] (1) The present invention adopts a novel liquid phase small molecule passivation technology, by which perfluoro(4-methyl-2-pentene) (C 6 F 12 ) was introduced as an additive into the green antisolvent to precisely modify MAPbI 3 Perovskite layer. C 6 F 12 Small molecules are liquids at room temperature, and their chemical formulas consist of carbon-carbon single bonds, double bonds, and carbon-fluorine bonds. 6 F 12 The fluorine in the perovskite can form a coordination bond with lead (Pb). At the same time, the strong electronegativity of the fluorine element enables it to form a hydrogen bond with the nitrogen in methylamine (MA). These two chemical bond / force mechanisms effectively fill the vacancies in the perovskite structure caused by the loss of iodine elements in the air environment. On the other hand, the inherent hydrophobicity of fluorine atoms gives the perovskite film prepared in the air environment excellent moisture resistance, thereby enhancing the stability of the final device.
[0021] (2) The C 6 F 12 Optimized high-quality MAPbI 3 The films exhibited improved crystallinity, increased grain size, reduced non-radiative recombination, and lower defect density. 3 The perovskite solar cells based on the nanostructured carbon nanotubes achieved a photoelectric conversion efficiency of up to 21.25% and almost negligible hysteresis effect. When the unencapsulated cells were placed in the dark at 85% humidity for 1000 hours, the C 6 F12 The optimized device showed excellent stability, maintaining 80% of its normalized PCE. This performance is significantly better than the unoptimized device, which only maintained 24% of its initial PCE. 6 F 12 When used as an anti-solvent modifier for perovskite films, efficient and stable perovskite solar cells can be prepared in an air environment without the need for a glove box. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor. Among them:
[0023] Figure 1 This is a flow chart for preparing the perovskite solar cell of Comparative Example 1.
[0024] Figure 2 It is a current density-voltage test curve diagram of the perovskite solar cells of Examples 1 to 3 of the present invention and Comparative Example 1.
[0025] Figure 3 MAPbI of Examples 1 to 3 of the present invention and Comparative Example 1 3 UV-Vis image of perovskite film.
[0026] Figure 4 MAPbI of Example 1 of the present invention and Comparative Example 1 3 SEM image of perovskite film.
[0027] Figure 5 MAPbI of Example 1 of the present invention and Comparative Example 1 3 PL spectrum of perovskite film.
[0028] Figure 6 The maximum steady-state photocurrent and stable PCE diagram of Example 1 of the present invention and Comparative Example 1.
[0029] Figure 7 The normalized power conversion efficiency diagram of Example 1 of the present invention and Comparative Example 1 (placed in a dark state at room temperature, 85% relative humidity, for 1000 hours).
[0030] Figure 8 It is a current density-voltage test curve diagram of the perovskite solar cells of comparative examples 2 to 4. DETAILED DESCRIPTION
[0031] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.
[0032] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0033] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.
[0034] Unless otherwise specified, all raw materials used in the examples of the present invention are commercially available, as shown in Table 1 for details.
[0035] Table 1
[0036]
[0037]
[0038] Among them, perfluoro(4-methyl-2-pentene)(C 6 F 12 The structure of ) (CAS No.: 2070-70-4) is shown in formula (1):
[0039]
[0040] Example 1
[0041] The present invention provides a device structure for preparing a perovskite thin-film solar cell with high humidity stability in an air environment:
[0042] Glass / ITO / SnO 2 / MAPbI 3 / Spiro-OMeTAD / Ag.
[0043] The anode is indium tin oxide (ITO), the hole transport layer is 2,2′,7,7′-tetrakis(N,N-dimethoxy-aniline)-9,9′-spirobifluorene (Spiro-OMeTAD), and the photoactive layer is methylamino lead iodide (MAPbI 3 ), the electron transport layer is tin dioxide (SnO 2 ), the cathode is silver (Ag);
[0044] The present invention provides a method for preparing a perovskite film with high humidity stability and a solar cell thereof:
[0045] (1) The original concentration of SnO was 15 wt.% 2 The hydrocolloid dispersion was diluted with deionized water to 3 wt.% and used as a precursor solution for the electron transport layer. After stirring at 300 rpm for 2 hours at room temperature, SnO 2 Precursor solution.
[0046] (2) 1M PbI 2 The MAI solid powder was dissolved in a mixed solvent of 0.6 ml N, N-dimethylformamide and 78 μl dimethyl sulfoxide as a perovskite precursor solution; it was then heated at 60 °C and stirred at 400 rpm for 1 hour before use.
[0047] (3) Add 30 μl of C 6 F 12 Dissolved in 1 ml of ethyl acetate (EA) as a modified green anti-solvent with a concentration of 3 vol%.
[0048] (4) FK209 and LiTFSI powders were dissolved in acetonitrile solvent at concentrations of 170 mg / ml and 150 mg / ml, respectively, and stirred at 350 rpm at room temperature for 2 hours to obtain FK 209 solution and LiTFSI solution as additives for Spiro-OMeTAD solution.
[0049] (5) 70 mg of Spiro-OMeTAD powder was dissolved in 1 ml of chlorobenzene solvent, and 25 μl of tBP solution, 55 μl of FK209 solution and 75 μl of LiTFSI solution were added as common additives. The mixture was then stirred at 200 rpm for 3 hours at room temperature to obtain a Spiro-OMeTAD solution.
[0050] (6) The ITO etched glass was ultrasonically treated with acetone, ethanol and isopropanol for 15 minutes respectively. After being fully dried on a heating table at 100°C, the substrate was treated with ultraviolet (UV) ozone for 15 minutes to completely eliminate the excess organic matter remaining on the surface.
[0051] (7) SnO as the electron transport layer (ETL) 2 The solution was spin-coated on a clean ITO-etched glass substrate at 3000 rpm for 30 seconds. After thermal annealing at 150°C for 25 minutes, the substrate was placed in an ultraviolet ozone environment for 15 minutes to obtain a dense electron transport layer.
[0052] (8) The heated and stirred perovskite precursor solution in step (2) was spin-coated on the dense SnO 2 Use the C prepared in step (3) 6 F 12 Modified ethyl acetate was added as a green anti-solvent to the perovskite layer 10 seconds before the end of the spin coating process to assist the crystallization of its grains. After a 30-minute thermal annealing treatment at 100°C to help the growth of perovskite crystals, a target perovskite film with high humidity stability in an air environment was obtained as described in this patent.
[0053] (9) To prepare a complete perovskite solar cell, a Spiro-OMeTAD solution as a hole transport layer was spin-coated on the perovskite layer at 4000 rpm for 30 seconds. In order to fully oxidize the Spiro-OMeTAD film after deposition, the substrate was placed in a desiccator overnight before evaporating the counter electrode.
[0054] (10) A layer with a thickness of about 75 nm and an active area of 0.06 cm was deposited on the top of the device by vacuum thermal evaporation. 2 Silver (Ag) is used as the top electrode. The complete device structure is: Glass / ITO / SnO 2 / MAPbI 3 / Spiro-OMeTAD / Ag perovskite solar cells.
[0055] The present invention discloses a method for preparing a perovskite film with high humidity stability and a solar cell thereof in an air environment. Except for the last step of vacuum evaporation of a silver electrode, all other steps are carried out in an air environment. The specific conditions are room temperature and a relative humidity of about 50%.
[0056] Example 2
[0057] The difference from Example 1 is that in step (3), C 6 F 12 As a modifier for ethyl acetate antisolvent.
[0058] Example 3
[0059] The difference from Example 1 is that in step (3), C 6 F 12 As a modifier for ethyl acetate antisolvent.
[0060] Comparative Example 1
[0061] The difference from Example 1 is that C is not used in step (3). 6 F12 As a modifier for ethyl acetate antisolvent. Figure 1 As shown, the preparation process of the perovskite solar cell (Comparative Example 1) is shown, and the effective area of the device is 0.06 square centimeters. 6 F 12 Its photoelectric performance and stability (anti-moisture ability) have been optimized and improved. It is worth noting that the overall preparation process is carried out at room temperature and in an atmospheric environment with a relative humidity of about 50% ± 5%. The absence of a glove box in this process indicates that there is no need to strictly control the inert atmosphere, which simplifies the manufacturing process and reduces costs.
[0062] Figure 2 The JV curves of the devices of Examples 1 to 3 and Comparative Example 1 are shown in Table 1. It can be seen that the photoelectric performance of the perovskite solar cells of Examples 1 to 3 is significantly better than that of Comparative Example 1, which is mainly manifested by the introduction of an appropriate amount of C 6 F 12 The power conversion efficiency (PCE) of the battery can be significantly improved. The battery performance of Example 1 is the best. Compared with Comparative Example 1, its short-circuit current J sc (24.21mA / cm 2 ), open circuit voltage V oc The values of the voltage (1.13V) and fill factor FF (77.68%) have been significantly improved.
[0063] Table 1 Main performance parameters of perovskite solar cells prepared in Examples 1 to 3 and Comparative Example 1
[0064]
[0065] Figure 3 MAPbI of Examples 1 to 3 and Comparative Example 1 3 UV-Vis spectrum of perovskite film. After 3 vol% concentration C 6 F 12 The light absorption spectrum of the modified perovskite layer (Example 1) is significantly improved compared with that of Comparative Example 1, showing its better light absorption ability. The reason for this enhancement is mainly due to its dense surface morphology, increased grain size and independent complete cross-sectional morphology. On the other hand, a small amount of 1 vol% concentration (Example 2) or a slightly excessive 5 vol% concentration (Example 3) of C 6 F 12 The additives can lead to a limited enhancement in their light absorption capacity. This phenomenon may be due to inappropriate additive dosages that lead to the degradation of MAI and PbI 2The unbalanced non-stoichiometric conditions in the solution state. Therefore, the crystallization of the perovskite grains and the film quality are unsatisfactory. The short-circuit current (Jsc) of the final device can be greatly improved from the higher sunlight utilization efficiency generated by the stronger light absorption ability of the perovskite film.
[0066] Figure 4 is the MAPbI of Example 1 and Comparative Example 1 3 Surface and cross-sectional SEM images of perovskite films, with a substrate structure of Glass / ITO / SnO 2 By applying the optimal 3 vol% concentration of C 6 F 12 (Example 1) The anti-solvent doped perovskite film obtained is obviously dense and uniform, characterized by increased grain size and reduced grain boundaries. The main factor leading to these enhancements is the optimal concentration C 6 F 12 The abundant electron donors can combine with the perovskite acceptors to occupy the vacancies in the I lattice, inhibit the formation of morphological defects, and promote the crystallization of perovskite grains. In contrast, the original MAPbI prepared in air environment, that is, under the negative influence of high humidity and other environmental factors, 3 The film (Comparative Example 1) has many small grains with more boundaries on its surface. This unsatisfactory morphology seriously affects the performance of the final device. On the other hand, the analysis of the two illustrations shows that the water contact angle of the perovskite film increases from 66.93° in the original layer to C 6 F 12 The modified layer has an angle of 87.44°, which reflects the excellent hydrophobicity brought by the fluorine element. It should be emphasized that all the manufacturing parameters of the perovskite layer, including the rotation speed and heating duration, were kept consistent.
[0067] MAPbI 3 The perovskite film was directly prepared on a glass substrate (without any conductive oxide) by spin coating and then subjected to PL testing, e.g. Figure 5 The PL spectrum test results clearly show that compared with the original perovskite layer (Comparative Example 1), the optimal concentration C 6 F 12 The PL intensity of the modified perovskite film (Example 1) was significantly enhanced. This significant improvement provides strong evidence for its suppressed non-radiative recombination.
[0068] The maximum steady-state photocurrent and stable PCE were measured at the maximum power point (MPP) of 0.94 V to evaluate the steady-state output capability of the device. Figure 6 As shown, C 6 F 12 The current density of the modified PSC was maintained at 23.02 mA / cm2 The stable level of the device with a corresponding stable PCE of 19.87% is much higher than that of the unmodified device (Comparative Example 1), which is consistent with the evaluation results of other perovskite films mentioned above.
[0069] like Figure 7 As shown, when the unpackaged device is placed in the dark at 85% relative humidity for 1000 hours, C 6 F 12 The optimized device showed excellent stability, maintaining 80% of its normalized PCE. This is significantly better than the unoptimized comparative example 1, which only maintained 24% of the initial PCE. The main reason for these significant improvements is C 6 F 12 Through its strong chemical bonds, it produces a dual passivation effect, enhancing the crystallization of perovskite grains and improving the overall quality of the film (including defect-free surface and dense cross-sectional morphology).
[0070] Comparative Example 2
[0071] The difference from Example 1 is that in step (1), C 6 F 12 Replaced with ethyl carbamate (EC).
[0072] Comparative Example 3
[0073] The difference from Example 1 is that in step (1), C 6 F 12 Replaced with liquid zwitterion (LTZ).
[0074] Comparative Example 4
[0075] The difference from Example 1 is that in step (1), C 6 F 12 Replaced with 4-(dimethylamino)-1-(2,2,2-trifluoroacetyl)pyridin-1-ium-2,2,2-trifluoroacetate (DTPT).
[0076] Table 2 Main performance parameters of perovskite solar cells prepared in Comparative Examples 2 to 4
[0077]
[0078] Figure 8 The JV curves of the devices of Comparative Examples 2 to 4 are shown in Table 2. It can be clearly seen that the power conversion efficiency of the final solar cells prepared by modifying perovskites with other liquid phase small molecules such as EC (PCE = 19.91%), LTZ (PCE = 20.75%) and DTPT (PCE = 20.06%) is lower than that of Example 1 (PCE = 21.25%). It should be emphasized that the data of various aspects (short circuit current Jsc , open circuit voltage V oc and fill factor FF) show a significant decrease compared with Example 1.
[0079] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the present invention.
Claims
1. A method for preparing a perovskite film with high humidity stability, characterized in that: include, The MAPbI3 perovskite precursor solution was spin-coated on the electron transport layer once and a modified anti-solvent was added 10 s before the end of the spin-coating process, and then subjected to thermal annealing treatment; The MAPbI3 perovskite precursor solution includes a solute and a solvent, wherein the solvent is a mixed solvent of N,N-dimethylformamide and dimethyl sulfoxide, and the solute is lead iodide and methylamino iodide; the modified anti-solvent is a solvent containing C6F 12 of ethyl acetate.
2. The preparation method according to claim 1, characterized in that: The C6F 12 The concentration is 0.1~6vol%.
3. The preparation method according to claim 1, characterized in that: The volume ratio of N,N-dimethylformamide to dimethyl sulfoxide in the solvent is 6:1-9:1, and the molar ratio of lead iodide to methylamino iodide in the solute is 1:
1.
4. The preparation method according to claim 1, characterized in that: The preparation method of the MAPbI3 perovskite precursor solution comprises: mixing a solute with a solvent, heating the mixture at 55° C. to 65° C., and stirring the mixture at a rotation speed of 200 to 500 rpm for 0.5 to 2 hours.
5. The preparation method according to claim 1, characterized in that: The primary spin coating conditions are: a rotation speed of 2000 rpm, a time of 10 s, a rotation speed of 3000 rpm, and a time of 25 s.
6. The preparation method according to claim 1, characterized in that: The annealing temperature is 90° C. to 110° C., and the annealing time is 10 to 40 minutes.
7. The preparation method according to claim 1, characterized in that: The volume ratio of the modified anti-solvent to the MAPbI3 perovskite precursor solution is 10:7 to 50:
7.
8. The perovskite film with high humidity stability obtained by the preparation method according to any one of claims 1 to 7, characterized in that: The thickness of the perovskite film is 200-600nm.
9. Use of the perovskite film with high humidity stability as claimed in claim 8 in perovskite solar cells.
10. The use according to claim 9, characterized in that: The perovskite solar cell includes an anode, an electron transport layer, a photoactive layer, a hole transport layer and a cathode; wherein the photoactive layer is between the anode and the cathode, the electron transport layer is between the anode and the photoactive layer; the hole transport layer is between the cathode and the photoactive layer; the anode is ITO, the electron transport layer is SnO2, the photoactive layer is MAPbI3, the hole transport layer is Spiro-OMeTAD, and the cathode is Ag. The complete device structure of the perovskite solar cell is Glass / ITO / SnO2 / MAPbI3 / Spiro-OMeTAD / Ag.